The clinical impact of nucleic acid amplification tests on the diagnosis and management of tuberculosis in a British hospital. Issue 4 (16th November 2007) - Taegtmeyer, M; Beeching, N J; Scott, J; Seddon, K; Jamieson, S; Squire, S B; Mwandumba, H C; Miller, A R O; Davies, P D O; Parry, C M
Abstract : Background: Nucleic acid amplification tests (NAAT) based on PCR provide rapid identification of Mycobacterium tuberculosis and the detection of rifampicin resistance. Indications for their use in clinical samples are now included in British tuberculosis guidelines. Methods: A retrospective audit of patients with suspected mycobacterial infection in a Liverpool hospital between 2002 and 2006. Documentation of the impact of NAAT usage in acid fast bacillus (AFB) microscopy positive samples on clinical practice and the influence of a multidisciplinary group on their appropriate use, compared with British guidelines. Results: Mycobacteria were seen or isolated from 282 patients and identified as M tuberculosis in 181 (64%). NAAT were indicated in 87/123 AFB positive samples and performed in 51 (59%). M tuberculosis was confirmed or excluded by this method in 86% of tested samples within 2 weeks, compared with 7% identified using standard methods. The appropriate use of NAAT increased significantly over the study period. The NAAT result had a clinical impact in 20/51 (39%) tested patients. Culture results suggest the potential for a direct clinical impact in 8/36 (22%) patients in which it was indicated but not sent and 5/36 (14%) patients for whom it was not indicated. Patients managed by the multidisciplinary group had a higher rate of HIV testing and appropriate use of NAAT. Conclusions: There were significant clinical benefits from the use of nucleic acid amplification tests in this low prevalence setting. Our data suggest that there would be additional benefit from their use with all AFB smear positive clinical samples.